Use of 3D Navigation in Subaxial Cervical Spine Lateral Mass Screw Insertion - Arab, Abdullah; Alkherayf, Fahad; Sachs, Adam; Wai, Eugene K. (Journal of Neurological Surgery Reports, 2018)
Objective Cervical spine can be stabilized by different techniques. One of the common techniques used is the lateral mass screws (LMSs), which can be inserted either by freehand techniques or three-dimensional (3D) navigation system. The purpose of this study is to evaluate the difference between the 3D navigation system and the freehand technique for cervical spine LMS placement in terms of complications. Including intraoperative complications (vertebral artery injury [VAI], nerve root injury [NRI], spinal cord injury [SCI], lateral mass fracture [LMF]) and postoperative complications (screw malposition, screw complications).Methods Patients who had LMS fixation for their subaxial cervical spine from January 2014 to April 2015 at the Ottawa Hospital were included. A total of 284 subaxial cervical LMS were inserted in 40 consecutive patients. Surgical indications were cervical myelopathy and fractures. The screws' size was 3.5 mm in diameter and 8 to 16 mm in length. During the insertion of the subaxial cervical LMS, the 3D navigation system was used for 20 patients, and the freehand technique was used for the remaining 20 patients. We reviewed the charts, X-rays, computed tomography (CT) scans, and follow-up notes for all the patients pre- and postoperatively.Results Postoperative assessment showed that the incidence of VAI, SCI, and NRI were the same between the two groups. The CT scan analysis showed that the screw breakage, screw pull-outs, and screw loosening were the same between the two groups. LMF was less in the 3D navigation group but statistically insignificant. Screw malposition was less in the 3D navigation group compared with the freehand group and was statistically significant. The hospital stay, operative time, and blood loss were statistically insignificant between the two groups.Conclusions The use of CT-based navigation in LMS insertion decreased the rate of screw malpositions as compared with the freehand technique. Further investigations and trials will determine the effect of malpositions on the c-spine biomechanics. The use of navigation in LMS insertion did not show a significant difference in VAI, LMF, SCI, or NRI as compared with the freehand technique.
Keywords: freehand; lateral mass screw; 3D navigation; cervical spine; subaxial spine; fixation complication